2016
DOI: 10.1016/j.bbi.2016.02.025
|View full text |Cite
|
Sign up to set email alerts
|

Stress impairs the efficacy of immune stimulation by CpG-C: Potential neuroendocrine mediating mechanisms and significance to tumor metastasis and the perioperative period

Abstract: We recently reported that immune stimulation can be compromised if animals are simultaneously subjected to stressful conditions. To test the generalizability of these findings, and to elucidate neuroendocrine mediating mechanisms, we herein employed CpG-C, a novel TLR-9 immune-stimulating agent. Animals were subjected to ongoing stress (20-hrs of wet cage exposure) during CpG-C treatment, and antagonists to glucocorticoids, β-adrenoceptor, COX2, or opioids were employed (RU486, nadolol, etodolac, naltrexone). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 39 publications
0
13
0
2
Order By: Relevance
“…After βAR activation, inflammation-dependent mechanisms remodel tumor-associated lymphatic and blood vasculature, which in turn promote in vivo tumor cell dissemination [36]. Also, accumulating evidence has suggested that catecholamines have a stronger effect upon the immune system than glucocorticoids, and activation of the sympathetic nervous system suppresses natural killer cell response to tumor cells [47, 48].…”
Section: Sympathetic Nervous System Activationmentioning
confidence: 99%
“…After βAR activation, inflammation-dependent mechanisms remodel tumor-associated lymphatic and blood vasculature, which in turn promote in vivo tumor cell dissemination [36]. Also, accumulating evidence has suggested that catecholamines have a stronger effect upon the immune system than glucocorticoids, and activation of the sympathetic nervous system suppresses natural killer cell response to tumor cells [47, 48].…”
Section: Sympathetic Nervous System Activationmentioning
confidence: 99%
“…In various animal models, CpG-ODN treatment was shown to reduce mammary lung metastases by eliciting antitumor natural killer (NK) activity [9], and even results in rapid debulking of large tumors by macrophage stimulation [10]. Employed prophylactically, CpG-ODNs were shown to markedly improve resistance to experimental and spontaneous peripheral metastasis of mammary [11], colon [12], and melanoma [13] tumors.…”
Section: Introductionmentioning
confidence: 99%
“…However, to implement a prophylactic approach against brain metastases in a wider range of patients, a less toxic [18] treatment is required. TLR9 stimulation using CpG-ODNs is particularly well suited to meet this need, as it has negligible toxicity in humans [1921], and has already promising preclinical outcomes in other organs [1013]; therefore, it should also be considered a potential prophylactic approach against the establishment of brain metastases.…”
Section: Introductionmentioning
confidence: 99%
“…The adverse systemic effects of chronic stress on immune cells, such as immunosuppression, might impair the positive therapeutic responses and benefits seen by current immunotherapies, highlighting the need to address SNS activation on tumor biology. For instance, ongoing stress can impair the efficacy of therapies based on immune stimulation (24, 128).…”
Section: Stress the Immune System And Potential Therapeutic Targetsmentioning
confidence: 99%